EFIKASI BIOINSEKTISIDA DAN KOMBINASINYA TERHADAP SERANGAN HAMA ULAT KANTONG Pagodiella spp. PADA BIBIT MANGROVE Rhizophora spp. DI PERSEMAIAN - Abd. Wahid (Universitas Tadulako, 2010)
The study of the efficacy of some bioinsecticides and their combinations to control Pagodiella spp. or bagworm attack on mangrove seedling was carried out in the seedling nursery of Malakosa and Sausu Peore Parigi Moutong, Central of Sulawesi, February to April 2008. A Nested design was applied in a Completely Randomize Design, where three levels of spraying intervals and eleven-application methods with three replications were used. The results showed that the application of microbial insecticides of Bacillus thuringiensis individually was effective in depressing Pagodiella spp. bagworm attacks (increasing of damage level 8,98% and 14,38%, respectively) also combination (increasing of damage level 11,36%). The combination applications among microbial insecticides and botanical insecticides were also effective in depressing Pagodiella spp. bagworm attacks. But both of the combination applications had no synergistic effect. Whereas the combination among botanical insecticides of mimba and sirsak were effective in depressing Pagodiella spp. bagworm attacks, which also produced synergistic effect (increasing of damage level 12,98%).